A Neonate with Subcutaneous Fat Necrosis after Passive Cooling: Does Polycythemia Have an Effect?. (9th July 2013) - Calisici, Erhan; Oncel, Mehmet Yekta; Degirmencioglu, Halil; Sandal, Gonca; Canpolat, Fuat Emre; Erdeve, Omer; Oguz, Serife Suna; Dilmen, Ugur
Abstract : Subcutaneous fat necrosis (SCFN) is an inflammatory disorder of adipose tissue. The main risk factors for the development of SCFN are perinatal asphyxia and hypothermia. Presented here is a case of a newborn who developed SCFN in association with polycythemia and hypocalcemia following treatment by passive cooling. Neonates who undergo passive or whole body cooling therapy should be closely monitored for any signs of SCFN.